Attitudes, Beliefs, Motivation and Identity in Mathematics Education An Overview of the Field and Future Directions - Hannula, Markku S.; Di Martino, Pietro; Pantziara, Marilena; Zhang, Qiaoping; Morselli, Francesca; Heyd-Metzuyanim, Einat; Lutovac, Sonja; Kaasila, Raimo; Middleton, James A.; Jansen, Amanda; Goldin, Gerald A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book records the state of the art in research on mathematics-related affect. It discusses the concepts and theories of mathematics-related affect along the lines of three dimensions. The first dimension identifies three broad categories of affect: motivation, emotions, and beliefs. The book contains one chapter on motivation, including discussions on how emotions and beliefs relate to motivation. There are two chapters that focus on beliefs and a chapter on attitude which cross-cuts through all these categories. The second dimension covers a rapidly fluctuating state to a more stable trait. All chapters in the book focus on trait-type affect and the chapter on motivation discusses both these dimensions. The third dimension regards the three main levels of theorizing: physiological (embodied), psychological (individual) and social. All chapters reflect that mathematics-related affect has mainly been studied using psychological theories.
Introduction -- Attitude -- Students' Self-efficacy Beliefs -- Teachers' beliefs -- Identity -- Motivation -- Further Reading on Mathematics Related Affect.
Keywords: 9; Educational psychology; Education-Psychology.; Mathematics Education; Educational Psychology